Pediatric invasive fungal rhinosinusitis - Villamor, Perla; Arango, Valeria; Cortes, Cristina; de la Torre, Carlos (Frontiers in Pediatrics, 2023)
Pediatric invasive fungal rhinosinusitis (PIFR) is a rapidly progressive, potentially fatal disease. Previous medical literature demonstrates that its early diagnosis significantly reduces the risk of mortality in these patients. This study aims to present an updated clinical algorithm for optimized diagnosis and management of PIFR. A comprehensive review was conducted with only original, full-text articles published in English and Spanish from Cochrane Library, Pub-Med/MEDLINE, Embase, Scopus, and Google Scholar between January 2010 and June 2022. Relevant information was extracted and then integrated to develop a clinical algorithm for a proper diagnosis and management of PIFR.